IDPlanT: the Italian database of plant translocation. (2nd November 2021) - Abeli, Thomas; D'Agostino, Martina; Orsenigo, Simone; Bartolucci, Fabrizio; Accogli, Rita; Albani Rocchetti, Giulia; Alessandrelli, Claudia; Amadori, Arianna; Amato, Filippo; Angiolini, Claudia; Assini, Silvia; Bacchetta, Gianluigi; et al.
Abstract: IDPlanT is the Italian Database of Plant Translocation, an initiative of the Nature Conservation Working Group of the Italian Botanical Society. IDPlanT currently includes 185 plant translocations. The establishment of a national database on plant translocation is a key step forward in data sharing and techniques improvement in this field of plant conservation. Supplemental data for this article is available online at https://doi.org/10.1080/11263504.2021.1985004 .